A Bibliometric scrutiny of Sustainability of Tourism in India - Akshay B. Ahlawat; Dr. Suresh Kumar (Innovative Research Thoughts, 2023)
Being the fourth engine of growth in a nation’s economy, tourism creates more than any other commensurate sector due to its elaborate back-end linkages. Over-tourism has been an extant issue for tourism thriving at tourist destinations for quite some time now. Thus, unsustainability of tourism is today a burning issue, causing greater probable distress for the future generations. Thus, a bibliometrics analysis using Biblioshiny tool of RStudio was conducted on the data retrieved from Scopus database for the years 1993 to 2022. An analysis of 136 such papers has been conducted depicting 15.96 percentage of annual growth with 353 authors from varied countries like India, USA, Australia among others. This study is deemed to benefit research scholars, managers, academicians and other personnel with relevant literature interest. The findings shall help assist in future course of research in such themes.